Improving Students’ Speaking Skill through Role-Play Technique in 21st Century - I Gusti Ayu Dwi Pradnyandari Pinatih (English Education Department STKIP Agama Hindu Singaraja, 2021)
Speaking is one of hard skill that should be mastered by students in English. In the speaking class, students faced several problems such as the learners show a low enthusiasm and motivation in speaking, afraid and shy to speak. It arises because of some factor such a low interest, material, and improper technique which apply in the class. In solving those problems, it needed an attractive teaching technique. The implementation of role-play as an appropriate teaching technique in the 21st century that can stimulate students in learning especially in speaking class can be one alternative. Role-play serve many advantages, one of them is to urge students in speaking. This study will use library research as the method for collecting the data. The findings show that role-play teaching technique strongly can improve students speaking skill in the classroom.